Emotional and Cultural Intelligence as Predictors of Collaborative Learning: Evidence from Undergraduate Education in Malaysia - Azzahrah, Anuar; Edris, Aden; Heng, Chin Siong; Mohamad Azhari, Abu Bakar (RSIS International, 2025)
Incorporating team-based assessments is widely regarded as essential for preparing students to navigate the challenges of their future professional careers. While previous studies have examined the role of emotional intelligence or cultural intelligence in collaborative learning, limited research has simultaneously explored how these two competencies interact in shaping students’ perceptions of team-based assessments, particularly within the undergraduate context. This study aims to examine the levels of emotional and cultural intelligence among undergraduate students, as well as their general attitudes toward courses that incorporate team-based assessments. A non-experimental, cross-sectional survey design was employed to achieve these objectives. A total of 223 undergraduate students participated in the study. The Schutte Emotional Intelligence and Cultural Intelligence instruments were administered for this study. The study further explores the relationship between emotional and cultural intelligence and students’ attitudes towards team-based assessments. The findings reveal significant correlations: emotional intelligence accounted for 32.8% and cultural intelligence accounted for 18.2% of the variance in students' attitudes toward team-based assessments. These results underscore the importance of emotional and cultural competencies in fostering greater student engagement in team-based learning environments.